A randomised phase 2 study comparing different dose approaches of induction treatment of regorafenib in previously treated metastatic colorectal cancer patients (REARRANGE trial). (December 2022) - Argilés, Guillem; Mulet, Nuria; Valladares-Ayerbes, Manuel; Viéitez, José M.; Grávalos, Cristina; García-Alfonso, Pilar; Santos, Cristina; Tobeña, María; García-Paredes, Beatriz; Benavides, Manuel; Cano, María T.; Loupakis, Fotios; et al.
Abstract: Purpose: The purpose of this article is to evaluate the safety of two regorafenib dose-escalation approaches in refractory metastatic colorectal cancer (mCRC) patients. Patients and methods: Patients with mCRC and progression during or within 3 months following their last standard chemotherapy regimen were randomised to receive the approved dose of regorafenib of 160 mg QD (arm A) or 120 mg QD (arm B) administered as 3 weeks of treatment followed by 1 week off, or 160 mg QD 1 week on/1 week off (arm C). The primary end-point was the percentage of patients with G3/G4 treatment-related adverse events (AEs) in each arm. Results: There were 299 patients randomly assigned to arm A (n = 101), arm B (n = 99), or arm C (n = 99); 297 initiated treatments (arm A n = 100, arm B n = 98, arm C n = 99: population for safety analyses). G3/4 treatment-related AEs occurred in 60%, 55%, and 54% of patients in arms A, B, and C, respectively. The most common G3/4 AEs were hypertension (19, 12, and 20 patients), fatigue (20, 14, and 15 patients), hypokalemia (11, 7, and 10 patients), and hand–foot skin reaction (8, 7, and 3 patients). Median overall survival was 7.4 (IQR 4.0–13.7) months in arm A, 8.6 (IQR 3.8–13.4) in arm B, and 7.1 (IQR 4.4–12.4) in arm C. Conclusions: The alternative regorafenib dosing schedules were feasible and safe in patients with mCRC who had been previously treated with standard therapy. There was a higher numerical improvement on the most clinically relevant AEs in the intermittent dosing arm, particularly during the relevant first two cycles. Clinicaltrials.gov identifier: NCT02835924. Highlights: Feasibility of two dose schedules of regorafenib initial deintensification in Europe. No improvement on the overall safety profiles was seen. A reduction in the most relevant AEs was observed (fatigue and HFSR). Efficacy was sustained across the experimental arms despite dose deintensification.